Proton-Coupled Electron tTransfer (PCET) with 1,4-Bisguanidino-Benzene derivatives: comparative study and use in acid-initiated C-H activation - Walter, Petra; Hübner, Olaf; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2021)
Proton-coupled electron transfer (PCET) is of key importance in modern synthetic chemistry. Redox-active guanidines were established by our group as valuable alternatives to toxic high-potential benzoquinones in a variety of different PCET reactions. In this work, the PCET reactivity of a series of 1,4-bisguanidino-benzenes varying in their redox potentials and proton affinities is evaluated. The relevant redox and protonation states are fully characterized, and the compounds sorted with respect to their PCET reactivity by comparative PCET experiments supplemented by quantum-chemical calculations. Depending on the studied reactions, the driving force is either electron transfer or proton transfer; thereby the influence of both processes on the overall reactivity could be assessed. Then, two of the PCET reagents are applied in representative oxidative aryl-aryl coupling reactions, namely the intramolecular coupling of 3,3’’-4,4’’-tetramethoxy-o-terphenyl to give the corresponding triphenylene, the intermolecular coupling of N-ethylcarbazole to give N,N’-diethyl-3,3’-bicarbazole, and in the oxidative lactonization of 2-[(4-methoxyphenyl)methyl]-benzoic acid. Under mild conditions, the reactions proceed fast and efficient. Only small amounts of acid are needed, in clear contrast to the corresponding coupling reactions with traditional high-potential benzoquinones such as DDQ or chloranil requiring a large excess of a strong acid.